Development of microstructure-sensitive damage models for zirconium polycrystals. (February 2022) - Abdolvand, Hamidreza
Highlights: A series of subroutines are developed to model crack nucleation and propagation in polycrystals. Four different damage mechanisms are incorporated in the damage model. The damage model is linked with a crystal plasticity finite element model to study microstructural effects. The calculated crack nucleation site from the maximum principal stress and the maximum slip methods coincides with the observed major crack. The calculated direction of the crack from the maximum slip method agrees with experimental results. Abstract: The incorporation of four different microstructure-sensitive damage mechanisms into a crystal plasticity finite element model is described in detail. The nucleation and propagation of cracks are based on (1) the local principal stress and normal to the corresponding principal plane, (2) the local principal plastic strain and normal to the corresponding principal plane, (3) the local maximum slip and normal to the predominant slip system, and (4) the energy stored in dislocations and normal to the predominant slip system. To study the performance of each model in predicting crack nucleation and propagation, the "as-measured" microstructure in the vicinity of a sharp notch in a pure zirconium specimen is imported into the crystal plasticity model. The numerical results are compared with those measured by the electron backscatter diffraction technique. This is followed by a numerical study of the effects of crystal orientation on the prediction of each model for a notched single crystal zirconium specimen. For the specimen texture studied here, results show that the principal stress and the maximum slip methods can correctly predict the location of major cracks, where only the latter replicates the correct direction of crack propagation. Predictions from the energy method or the principal plastic strain method mainly coincide with the minor cracks or those that propagate at higher applied strains.